Diagnosis and treatment of syphilis: an investigation with women seen in primary carein Sobral, Ceará - Cavalcante, Ana Egliny S.; Silva, Maria Adelane M.; Rodrigues, Antonia Regynara M.; Mourão Netto, José Jeová; Moreira, Andréa C.A.; Goyanna, Natália F. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: syphilis is a sexually transmitted disease which affects almost all organs and systems of our body. Although it has an affective and low cost treatment, it remains a public health problem until nowadays. It has a high incidence among women and its control is a big challenge because of the social implications. Objective: to know the experience of women who carry syphilis, accompanied by the family health system in the city of Sobral. Methods:this is an exploratory qualitative study involving seven women who were undergone to a syphilis treatment in a health center in Sobral. The information was collected by means of a semi-structured interview and the results were analyzed according to a categorizing technique of their speeches. The research has met the scientific and ethical requirements for a work involving people. Results: the results were analyzed according to three categories: the knowledge about the disease, impressions about syphilis and difficulties faced due to Syphilis. It was found that the participants do not know much about that disease and its incident results in a negative impact on women’s lives, involving their social coexistence and their family relationships, mainly their partners. Conclusion: the diagnostic of a sexually transmitted disease, particularly syphilis, for most women, results in negative feelings and fear of being a target of prejudice from their partners and society, resulting on psychological and emotional problems.